TRADITIONAL PARENTING Seeing Early Childhood Parenting of Sambas Malays - Bayu Suratman; Maemonah Maemonah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2021)
This article is based on the results of in-depth research related to the nurturing of the Sambas Malay ethnicity in the villages of Sambas Regency. The traditional parenting performed by the Sambas Malay ethnic parents in the villages is still ongoing today. This paper discusses how traditional care for early childhood still exists in rural Sambas District. This research was conducted using a qualitative method through a sociological approach. Data obtained through interviews and in-depth observations in the villages of Semparuk and Tebas districts, Sambas districts. The results of this study indicate that the Samba Malay ethnic children play with traditional games. In addition, the parenting that works as farmers invites their children to go to the fields. Bringing children to the fields is part of introducing children to nature. Finally, the Malay Sambas parents provide care in the form ofpoint out pronunciation, namely teaching children at an early age, especially when they are still babies, by inviting children to talk, sing songs, dhikr, and say poetry.